Faktor-Faktor Yang Mempengaruhi Hipertensi Pada Ibu Hamil Di Wilayah Kerja Puskesmas Legonkulon Kabupaten Subang - Karimah, Karimah; Rokmah, Siti (Akademi Kebidanan Bunga Husada Samarinda, 2024)
The Maternal Mortality Rate (MMR) in Indonesia is still relatively high. Hypertension in pregnancy often occurs and is one of the causes of maternal death. The problem in Indonesia is that hypertension in pregnancy is the second highest cause of death after bleeding. The aim of the research is to see the relationship between age, parity, stress, obesity, physical activity and history of hypertension with the incidence of hypertension in pregnant women in the Legonkulon Regency Work Area. This research is in accordance with the road map of the study program and lecturers and is in accordance with the advantages of the PSDKU Subang D3 Midwifery study program. The research method is observational analytics with a case control approach. The sampling technique used purposive sampling which met the inclusion and exclusion criteria of 60 pregnant women. The data collection technique uses a questionnaire technique, namely collecting data containing demographic data, parity, stress, obesity, physical activity, and history of hypertension, using a list of questions related to research that has been prepared previously and given directly to respondents to be filled in according to the questionnaire instructions or researcher direction. The conclusion of the research was that there was a relationship between parity, stress, obesity, and a history of hypertension with the incidence of hypertension in pregnant women in the Community Health Center Work Area. However, there is no relationship between physical activity of pregnant women and the incidence of hypertension in pregnant women in the Puskesmas Work Area. Output, publication of national journals with ISSN or reputable journals and will produce posters for early detection of hypertension in pregnant women.